Thermal-induced damage mechanisms and permeability evolution in gneiss for deep mining applications - Zhang, Jian; Hu, Zilong; Liu, Dakang; Qiu, Ji; An, Ran (Frontiers in Earth Science, 2025)
With the rapid development of deep mining and geothermal exploitation, the influence of high-temperature environment on the mechanical properties of rocks has become a core challenge for engineering safety. This study focuses on gneiss (a common rock type in deep mining environments) to systematically investigate the thermal effects (25°C–800°C) on multiscale structural damage and permeability evolution. Through integrated experimental approaches including high-temperature treatment, uniaxial compressive strength tests, micro-CT scanning, scanning electron microscopy (SEM) analysis, and digital seepage simulations, we comprehensively characterize the temperature-dependent structural alterations and fluid transport properties. The results indicate that as the temperature increases, the mass loss rate and porosity of gneiss significantly increase, and the heterogeneity of pore distribution intensifies. Thermal cracks gradually coalesce and form macroscopic fracture surfaces above 600°C, leading to an increase in volumetric porosity from 1.87% to 6.78%. Seepage simulation reveals that the absolute permeability increases by approximately 135% at 800°C, showing a linear positive correlation with the total porosity. Microscopic analysis reveals that the evaporation of intercrystalline bound water and differential thermal expansion of minerals are the main causes of crack propagation, and the compressive strength of the rock decreases by 35.6% at high temperatures. This study innovatively combines X-CT scanning technology with digital core analysis to establish a three-dimensional quantitative evaluation system for gneiss fractures under high-temperature conditions, offering theoretical and technical support for deep mining engineering.